The Challenges of teaching English pronunciation in multicultural classroom: the voice of EFL teachers - Kamengko, Daniel Frengky; Beeh, Norci; Ludji, Ifoni; Meha, Agus Maramba (Jurnal Edulanguage: Jurnal Pendidikan Bahasa, 2024)
This study aims to examine the obstacles faced by English EFL teachers when teaching pronunciation in a multicultural classroom setting. Employing a qualitative case study design, data was collected through observations and interviews with two senior English teachers from SMP Negeri 10 Kota Kupang. The analysis was conducted using vivo coding. Key challenges include lack of confidence, knowledge, and training, as well as time constraints and the low prioritization of pronunciation in the curriculum. Teachers expressed apprehension about making pronunciation errors, which undermined their confidence in teaching pronunciation. Additionally, they reported inadequate knowledge of English pronunciation, contributing to their lack of confidence. Moreover, teachers were uncertain about the significance of pronunciation in English teaching and faced difficulties in finding sufficient time to cover all required syllabus topics, leaving little room for pronunciation practice. The dearth of teaching materials and resources tailored to individual student needs further exacerbated these challenges. The study concludes that addressing these challenges necessitates the support of educational authorities. Recommendations include providing targeted training sessions to enhance teachers' pronunciation teaching skills and incorporating pronunciation into English school assessments. By addressing these needs, educational institutions can better support teachers and enhance pronunciation instruction in multicultural classrooms.